The Effect of Nearpod-Based Learning Media on Students’ Learning Interest and Learning Outcomes - Anisa; Isnawati Lujeng Lestari (Noumerico: Journal of Technology in Mathematics Education, 2026)
This study aims to develop a Nearpod-based mathematics learning media that is valid, practical, and effective in increasing the interest and learning outcomes of Grade X students at MA NU Lekok. The development model used is the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The instruments used in the research include expert validation sheets, practicality questionnaires, learning interest questionnaires, and pretest and posttest questions. The validation results from subject-matter and media experts indicated that the media falls into the "very valid" category. A limited-scale practicality test obtained a score of 90%, showing that the media is highly practical for classroom use. The effectiveness of the media was demonstrated by improved student learning outcomes, as evidenced by pretest and posttest scores, and by increased interest in learning, as measured through questionnaires. The t-test results showed a significant difference between the pretest and posttest scores. Therefore, the Nearpod-based learning media is effective in improving students’ interest and learning outcomes.